АНЕМИЧЕСКИЙ СИНДРОМ В КЛИНИЧЕСКОЙ ПРАКТИКЕ: ПРИНЦИПЫ ДИАГНОСТИКИ - Ю. Л. Шевченко; В. Я. Мельниченко; Д. А. Федоренко (Архивъ внутренней медицины)
Anemia is the most common blood disorder. There are several kinds of anemia, produced by a variety of underlying causes. Anemia can be classified in a variety of ways, based on the morphology of red blood cells and underlying etiologic mechanisms. Anemia goes undetermined in many people, and symptoms can be minor or vague. The signs and symptoms can be related to the anemia itself, or the underlying causes. This article is about the main principles of diagnosis of anemia in clinical practice. We hope that this information will help to diagnose the different types of anemia in daily clinical practice.